2018
DOI: 10.3389/fnins.2018.00507
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms With Respect to Different Paradigms and Relevant Regulatory Factors in Empathy for Pain

Abstract: Empathy for pain is thought to activate the affective-motivational components of the pain matrix, which includes the anterior insula and middle and anterior cingulate cortices, as indicated by functional magnetic resonance imaging and other methodologies. Activity in this core neural network reflects the affective experience that activates our responses to pain and lays the neural foundation for our understanding of our own emotions and those of others. Furthermore, although picture-based paradigms can activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 79 publications
0
39
0
1
Order By: Relevance
“…How does the involvement of self-interest regulate empathic responses toward others who suffer unfair treatment? It has been suggested that empathy involves both an early automatic component characterized by emotional sharing (bottom-up processing) and a late controlled component characterized by cognitive evaluation (top-down processing) (Decety and Lamm, 2006; Shamay-Tsoory et al, 2007, 2009; Xiang et al, 2018). This raises the question, ‘Which component is more likely to be affected by self-interest?’ Addressing this issue could help to resolve some of the gaps and apparent anomalies in the current literature on empathy.…”
Section: Introductionmentioning
confidence: 99%
“…How does the involvement of self-interest regulate empathic responses toward others who suffer unfair treatment? It has been suggested that empathy involves both an early automatic component characterized by emotional sharing (bottom-up processing) and a late controlled component characterized by cognitive evaluation (top-down processing) (Decety and Lamm, 2006; Shamay-Tsoory et al, 2007, 2009; Xiang et al, 2018). This raises the question, ‘Which component is more likely to be affected by self-interest?’ Addressing this issue could help to resolve some of the gaps and apparent anomalies in the current literature on empathy.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that empathy involves both an early automatic component characterized by emotional sharing (bottom-up processing) and a late controlled component characterized by cognitive evaluation (top-down processing) ( Decety and Lamm, 2006 ; Xiang et al, 2018 ). Evidences from ERP studies have shown that the temporal dynamics of empathy for pain consists of an early affective arousal component (N1/N2) followed by a late cognitive reappraisal and regulation component (P3/LPP) ( Luck and Hillyard, 2000 ; Fan and Han, 2008 ; Han et al, 2008 ; Cheng et al, 2017 ; Decety et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The neural areas, aMCC and insula, which support the affective experience of pain (e.g., Jackson et al, 2006b , Xiang et al, 2018 ), did not in fact show a supra-threshold difference in activation between groups. Moreover, aMCC and insula were not hyper-reactive to perceived pain in others relative to self, contrary to previous research, ( Jackson et al, 2006a , Lamm et al, 2007 , Singer et al, 2004 ).…”
Section: Discussionmentioning
confidence: 86%
“…Activation of somatosensory cortex when observing stimuli depicting the delivery of pain to different body area is suggested to represent the brain substrate of pain perception and its location on the body ( Xiang et al, 2018 ). In parallel, anterior insula and aMCC are implicated in mediating the affective-motivational components of pain processing as reported by Jackson et al (2006a) and subsequently confirmed in a meta -analysis report of 32 such studies ( Lamm et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation